The Effectiveness Of Leaflet Education Media On Knowledge And Attitudes Regarding Health Protocol During The Covid 19 Pandemic In Canrego Village, South Polongbangkeng District, Takalar District - Kamriana, Kamriana; Dewiyanti, Dewiyanti; Arafah, Salmah; Alwi, Alwi (Journal of Midwifery and Nursing, 2024)
Since the end of December 2019, the disease known as Covid-19 originated in Wuhan, a city located in China. Animals and humans share this virus. Humans can spread this disease through their respiratory system. Flu, coughs and more severe symptoms from SARS (Severe Severe Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome) are all possible causes. Corona is a new type of disease that originated in China and has just been discovered (WHO, 2019). Research objectives: In South Polongbangkeng village, Takalar Regency, to determine the impact of leaflet educational media on knowledge and attitudes regarding health protocols during the Covid-19 pandemic. sampling and quasi-experimental design with one group design before and after the test were used in the research design and methods. utilized an accidental sampling approach to select a sample of thirty respondents. At a significance level of p 0.05, the Wilcoxon test was used to analyze the data. Research Results: Research findings are based on attitudes about health protocols during the corona disease pandemic and knowledge about health protocols during the COVID 19 pandemic, both before and after the leaflets were distributed to the general public (p = 0.000). Conclusion: In Canrego Village, South Polongbangkeng District, Takalar Regency, the distribution of educational leaflets influenced knowledge and attitudes about health protocols during the Covid 19 pandemic